Diffuse Lung Diseases Clinical Features, Pathology, HRCT - Maffessanti, Mario; Dalpiaz, Giorgia (Springer Milan : Imprint: Springer, 2006)
This book aims to help the reader who is confused by the multiplicity of diseases with similar symptoms in different patients. Consequently, the chapters are noticeably sign-oriented rather than disease-oriented, each dealing with one of the four cardinal modalities of HRCT presentation;, namely, the reticular, nodular, alveolar and cystic patterns. Each chapter is introduced by a list of diseases, immediately followed by a detailed description, thoroughly illustrated. Each isThe chapters are thoroughly illustrated with high-quality, enlarged images, which, like counterpoint, provide the rhythm to the written text. When dealing with the diseases within each pattern, only the pertinent of themones are taken into account. This is a feature unique to this book, which sees the same disease being introduced even two or three times. Often, clinical presentation, history and HRCT are sufficient for making a diagnosis and defining disease management; in other cases, further investigation is required to obtain a more confident diagnosis, or to stage grade the activity of the disease more precisely. Consequently, the contribution of other techniques involved in diagnostic refinement are highlighted (bronchoalveolar lavage, bronchoscopic or thoracovideoscopic biopsy, open chest surgery).